Diabetes care in pediatric refugees from Africa or Middle East: experiences from Germany and Austria based on real-world data from the DPV registry. Issue 1 (July 2019) - Prinz, Nicole; Konrad, Katja; Brack, Christoph; Hahn, Eva; Herbst, Antje; Icks, Andrea; Grulich-Henn, Jürgen; Jorch, Norbert; Kastendieck, Christian; Mönkemöller, Kirsten; Razum, Oliver; Steigleder-Schweiger, Claudia; et al.
Abstract : Objective: With increasing migration to Europe, diabetes diagnosis and treatment of refugees became challenging. To describe the current experience with pediatric refugees in Germany and Austria. Design and Methods: 43, 137 patients (<21 years) with type 1 diabetes from the diabetes patient follow-up registry (DPV) were studied and divided by refugee status into patients born in Middle East ( n  = 365) or Africa ( n  = 175) and native patients (child and parents born in Germany/Austria; G/A: n  = 42, 597). Groups were compared using multivariable regression adjusted for age, sex and diabetes duration (SAS 9.4). In refugees the first year after arrival was studied, and for native children the most recent year of care. Results: After adjustment, HbA1c was highest in refugees (1. ME and 2. AFR vs 3. G/A: 72.3 ± 1.0 and 75.0 ± 1.4 vs 66.0 ± 0.1 mmol/mol, 1 vs 3: P  < 0.001 and 2 vs 3: P  < 0.001) and microalbuminuria (9.9 and 13.6 vs 6.5%, 1 vs 3: P  = 0.039 and 2 vs 3: P  = 0.002) was more prevalent. African children experienced severe hypoglycemia (17.8 ± 4.3 and 25.4 ± 8.7 vs 11.5 ± 0.3 per 100 patient years, 1 vs 3: P  > 0.05 and 2 vs 3: P  = 0.045) significantly more often, whereas hypoglycemia with coma (5.1 ± 1.1 and 4.1 ± 1.6 vs 2.6 ± 0.1 per 100 patient years, 1 vs 3: P  = 0.006 and 2 vs 3: P  > 0.05) and retinopathy (2.1 and n/a vs 0.2%, 1 vs 3: P  < 0.001) were significantly more common in children from Middle East compared to natives. Insulin pumps were used in a markedly larger proportion of native patients (7.4 and 13.2 vs 43.0%, 1 vs 3: P  < 0.001 and 2 vs 3: P  < 0.001). Conclusions: A relevant number of pediatric refugees with type 1 diabetes are treated in German/Austrian diabetes clinics. Refugee children, parents and caregivers are faced with several problems in diabetes therapy and outcome that should be addressed more intensively by pediatric diabetes teams.